Do Demographic Factors Affect Digitial Financial Literacy? - Fida Muthia; Agil Novriansa; Sri Andaiyani (Faculty of Economics, Universitas Sriwijaya, 2023)
The purpose of this study is to determine the socio-economic influence on digital financial literacy. This research also focuses on differences in digital financial literacy by age category. Data analysis in this study was carried out using Structural Equation Modeling (SEM) through AMOS software to see the causal relationship between variables. Meanwhile, the one-way ANOVA test was used to see differences in digital financial literacy by age category. The results showed a negative and significant relationship between socio-economic factors and the level of digital financial literacy based on age and also found to have a significant difference. This research suggests policy makers to consider digital financial literacy as part of the knowledge offered at schools or universities.